Effectiveness of Brand Image, Content Marketing, and Quality Product on Purchase Decision of J-GLOW Products - Sisca Dwintri Nata; Tri Sudarwanto (Journal of Economics and Business Aseanomics (JEBA), 2022)
This study intends to investigate the relationship between brand image, content marketing, and product quality in influencing Surabaya consumers' decisions to purchase J-GLOW skin care and cosmetic items. This study employed a quantitative survey methodology. Multiple regression analysis was used to analyze an association between brand image and purchasing the J-GLOW product. The content marketing variable has no relationship with J-GLOW product purchase decisions. Meanwhile, product quality influences the choice of the J-GLOW skin care product. It is indicated by the fact that the F-count value is greater than the F-table value (22,763 3,10), and the actual value is less than the alpha value (0.000 0.05). It demonstrates that characteristics such as brand image (X1), content marketing (X2), and product quality (X3) have a significant impact on purchasing decisions. According to the findings of the study, the brand image (X1), content marketing (X2), and product quality (X3) variables had a 45.7% impact on the decision to purchase J-GLOW products. Additional factors influenced the remaining 54,3%.